KEMAMPUAN PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE - AMBARWATI, RIYAMA; PUTRA, RIZKI WAHYU YUNIAN; KHASANAH, NURUL; JL, ANA RISQA; ALHAQ, ARINI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This study aims to determine ; 1) differences in the ability to understand concepts and critical mathematical thinking abilities through the picture and picture learning model, 2) differences in abilities to understand concepts through the picture and picture learning model, and 3) differences in mathematical critical thinking abilities through the picture and picture learning model. This research was conducted at MTs Negeri 1 Mesuji. The type of research used was quasi-experimental with a posttest only control group design. Data analysis used the MANOVA test. Based on the research results, it was concluded that there were differences in the ability to understand concepts and mathematical critical thinking abilities through the picture and picture learning model, there were differences in the ability to understand concepts through the picture and picture learning model, and there were differences in mathematical critical thinking abilities through the picture and picture learning model. ABSTRAKPenelitian ini bertujuan untuk mengetahui ; 1) perbedaan kemampuan pemahaman konsep dan kemampuan berpikir kritis matematis melalui model pembelajaran picture and picture, 2) perbedaan kemampuan pemahaman konsep melalui model pembelajaran picture and picture, dan 3) perbedaan kemampuan berpikir kritis matematis melalui model pembelajaran picture and picture. Penelitian ini dilakukan di MTs Negeri 1 Mesuji. Jenis penelitian yang digunakan adalah quasi eksperimen dengan desain posttest only control group design. Analisis data menggunakan uji MANOVA. Berdasarkan hasil penelitian disimpulkan bahwa terdapat perbedaan kemampuan pemahaman konsep dan kemampuan berpikir kritis matematis melalui model pembelajaran picture and picture, terdapat perbedaan kemampuan pemahaman konsep melalui model pembelajaran picture and picture, dan terdapat perbedaan kemampuan berpikir kritis matematis melalui model pembelajaran picture and picture.